PERANCANGAN KOMIK FIKSI GATOTKACA SANG KSATRIA PEWARIS - TOMI ADISON, Dra. Jupriani, M.Sn., Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Currently, many superhero films that picked up the story as a story, fiction superhero film with the story of these preferred by many people in Indonesia, especially by teenagers. Superhero tale presented in the homeland at this time many came from the American company Marvel and DC. Of the many superhero who became an idol rarely found from the ground water.Fiction comic design objectives Ghatotkacha the Knights Heir and comics also selected as the primary medium for comics can convey the message effectively and what can be delivered immediately understood without having to think about it as a textbook, nor a novel. When compared to novels, comics advantages lies in the visualization.The method used dperancangan this comic qualitative data analysis methods used in the design of the comic's author using 5W1H (what, where, who, why, when, how). The author conducted an analysis of the Knights of comic fiction Heir Ghatotkacha that has never been made before. As a study in designing comics and supported by media support in the form of x-banners, posters, flags Chain, pins, stickers, bookmarks, key chains, Paper Bag, and a covered plastic glasses, which can promote the comic Fiction Billy Glass Knight Heir.Keywords: Puppet Story, Gatotkaca the heir knight, Comic Fiction.